1984
DOI: 10.1128/aac.25.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the nucleoside analog 2'-nor-2'-deoxyguanosine on human cytomegalovirus replication

Abstract: The nucleoside analog 2'-nor-2'-deoxyguanosine (2'NDG) effectively inhibits the replication of several laboratory and clinical isolates of human cytomegalovirus. These isolates included viruses obtained from congenitally infected infants and patients suffering from acquired immune deficiency syndrome. The dose of 2'NDG that inhibited cytomegalovirus plaque formation ranged from 0.1 to 1.6 ,ug/ml. At 10 ,ug/ml, 2'NDG completely blocked the production of virus progeny but not the expression of immediate early an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…The results from our studies agree with previously reported data (2,28) that GCV is an effective inhibitor of the production of infectious HCMV as measured by the plaque reduction assay. From the results of in vitro studies, it has -suu * 'P ---Probe, Hindill been assumed that GCV reduces the production of infectious virions by inhibiting viral DNA polymerase (15,21).…”
Section: Discussionsupporting
confidence: 83%
“…The results from our studies agree with previously reported data (2,28) that GCV is an effective inhibitor of the production of infectious HCMV as measured by the plaque reduction assay. From the results of in vitro studies, it has -suu * 'P ---Probe, Hindill been assumed that GCV reduces the production of infectious virions by inhibiting viral DNA polymerase (15,21).…”
Section: Discussionsupporting
confidence: 83%
“…Acyclic nucleoside analogs have been reported to have lower activities against CMV than against HSV or varicella zoster virus (1,10). Therefore, it was surprising that 9-(1,3-dihydroxy-2-propoxymethyl)guanine (DHPG) was a much more potent inhibitor of CMV multiplication in cell culture than 9-(2-hydroxyethoxymethyl)guanine (ACV) (18,24). The triphosphates of these analogs, DHPGTP and ACVTP, were inhibitors of the partially purified CMV DNA polymerase.…”
mentioning
confidence: 99%
“…However, few inhibitors of human cytomegalovirus (HCMV) have been reported so far (1,5,6,17). Since HCMY does not induce viral thymidine kinase, antiviral nucleoside analogs, which are dependent on conversion to their 5'-triphosphate forms by viral thymidine kinase, cannot inhibit HCMV replication.…”
mentioning
confidence: 99%